Application of Target Costing method in the Hospitality Industry - Pajrok, Andor (Journal of Education Culture and Society, 2020)
Traditional approaches to managing costs are based on the costs that are the result of existing capabilities and resources in the company. Adding to these costs a specified margin or profit, leads to the sales price. If the market is not ready to accept such a selling price, managers need to find opportunities for rationalization and cost reduction. Target cost management begins the process of managing the sales price and the planned profit that the market can accept, and only then is it possible to determine the cost of the product. In the planning phase of the product and the manufacturing process the approach is to finding a method to lower costs and to reduce them as much as possible. The aim this of study is to investigate the application of target (strategy) cost accounting methods in the Hospitality Industry.